Effect of plant geometry on rabi and kharif onion production - S R Bhonde, R K Singh, (Journal of Spices and Aromatic Crops, 2014)
The experiment was conducted to evaluate the effect of plant geometry on production of onion bulbs during rabi 2008–09 and kharif–2009. Eight week old seedlings of variety Agrifound Light Red in Rabi and seven week old seedlings of variety Agrifound Dark Red in kharif were transplanted in raised beds during the last week of December in rabi and August in kharif in different geometry i.e. S1- Normal planting 15 cm × 10 cm whole bed, straight row, S2-Zig zag planting 2 rows 30 cm × 10 cm whole bed, S3- Straight strip planting 10 cm × 10 cm (one strip 4 rows between strip 30 cm), S4-Zig zag strip planting 20 cm × 10 cm (one strip 4 rows between strip 30 cm) and S5-Paired row planting 30 cm × 10 cm (2 rows between pair 20 cm. Rabi data revealed that significantly higher equatorial bulb diameter (5.61 cm), polar diameter (3.93 cm), bulb size index (22.07 cm2), and 20 bulb weight (1.38 kg) were noted in S5 and was at par with S4 (5.59 cm), (3.90 cm), (21.87 cm2) and (1.33 kg), respectively. Treatment S5 showed highest total soluble solids (12%) and dry matter content (14%). Significantly highest gross yield (305 q ha-1) and marketable yield (291 q ha-1) were noted in S5 and was at par with S4 (302 q ha-1) and (205 q ha-1), respectively. In kharif, highest plant height (61.00 cm) was observed for S5-Paired row planting 30 cm × 10 cm (2 rows between pair 20 cm) which was, however, at par with S1-Normal planting 15 cm × 10 cm whole bed, straight row, and S4-Zig zag strip planting 20 cm × 10 cm (one strip 4 rows between strip 30 cm). The highest equatorial bulb diameter (5.42 cm), polar diameter (4.12 cm), 20 bulbs weight (1.18 kg) and bulb size index (22.28 cm2) were noted in S5- Paired row planting 30 cm × 10 cm (2 rows between pair 20 cm). The minimum thrips incidence (58 %) and number of thrips per plant (3) were noted in S5- Paired row planting 30 cm × 10 cm (2 rows between pair 20 cm). Highest and significant gross yield (226 q ha-1) and marketable yield (207 q ha-1) were noted in S5. It is concluded from the experiment that S5-Paired row planting 30 cm × 10 cm (2 rows between pair 20 cm) gave better results over other geometry in rabi as well as in kharif.